Association between metal cobalt exposure and the risk of congenital heart defect occurrence in offspring: a multi-hospital case-control study - Nannan Zhang; Shuihua Yang; Jiaxiang Yang; Ying Deng; Shengli Li; Nana Li; Xinlin Chen; Ping Yu; Zhen Liu; Jun Zhu (Komiyama Printing Co. Ltd, 2020)
Abstract Background Many studies have investigated heavy metal exposure could increase the occurrence of congenital heart defects (CHDs). However, there are limited data regarding the relationship between cobalt exposure and CHD occurrence in offspring. The aim of this study was to analyze the association between cobalt exposure in mothers and the risk of CHDs in offspring. Materials and methods In order to explore the association between cobalt exposure and occurrence of congenital heart defect (CHD), a case-control study with 490 controls and 399 cases with CHDs in China were developed. The concentrations of cobalt in hair of pregnant woman and fetal placental tissue were measured and processed by a logistic regression analysis to explore the relationship between cobalt exposure and risk of CHDs. Results The median concentration of hair cobalt in the control and case group was 0.023 ng/mg and 0.033 ng/mg (aOR, 1.837; 95% CI, 1.468-2.299; P < 0.001), respectively. And the median (5-95% range) fetal placental cobalt concentrations were 19.350 ng/g and 42.500 ng/g (aOR, 2.924; 95% CI, 2.211-3.868; P < 0.001) in the control and case groups, respectively. Significant differences in the middle level of cobalt in hair were found in the different CHD subtypes, including septal defects, conotruncal defects, right ventricular outflow tract obstruction, and left ventricular outflow tract obstruction (P < 0.001). Dramatically, different cobalt concentrations in fetal placental tissue were found in all subtypes of cases with CHDs (P < 0.01). Conclusions The finding suggested that the occurrence of CHDs may be associated with cobalt exposure.